Pengaruh Lokasi, Cita Rasa, dan Harga Terhadap Keputusan Pembelian di Sate Pak Eko Satak Kecamatan Puncu Kediri - Anassuri, Khoirunnisa; Pramutoko, Baju; Afrianto, Dadang (Populer: Jurnal Penelitian Mahasiswa, 2023)
This research explains the influence of location, taste and price on purchasing decisions at Sate Pak Eko Satak, Puncu Kediri District. The method in this research is the quantitative method and the technical analysis used is validity test, reliability test, correlation test, multiple linear regression analysis, t test (partial test), f test (simultaneous test), and R2 coefficient of determination test. The population in this study was 100 respondents. The sample collection technique in this research used incidental sampling (a technique for determining samples based on chance) and the number of samples used was 100 respondents. In this research, the results showed that location had no partial and significant influence on purchasing decisions, taste had a partial and significant influence on purchasing decisions, and price had a partial and significant influence on purchasing decisions. Furthermore, location, taste and price together have a big relationship to purchasing decisions, and location, taste and price have a simultaneous and significant influence on purchasing decisions.